Dental molding compounds and casts: Use in non-laboratory environments - Rebecca Scopa Kelso; Brannon I Hulsey; Kathryn R.D. Driscoll (Dental Anthropology Association, 2020)
Dental casts are invaluable research tools. There are a variety of molding compounds available, all having temperature, humidity, and timing guidelines to ensure a precise replica of dentition. However, not all field research conditions allow for adherence to environmental guidelines requiring longer wait times prior to pouring epoxy for casting. This study, tests a common molding compound in extreme environments and over varying time intervals, testing the integrity of the dental molds in producing precise replicas of original teeth. 580 molds were created under three varying environments: room temperature, hot/humid, and cold/dry. Molds were removed from these environments in two-week intervals over twelve weeks. The resulting casts were measured to determine timing limitations for producing accurate dental casts under varying environments. Molds stored at room temperature retained their shape and size for the complete twelve weeks. Molds kept in a hot and humid environment, however, only maintained their shape and size up to four weeks, whereas molds in a cold and dry environment showed significant changes by the end of the second week. These findings provide additional tools for researchers working in a variety of field conditions allowing casts to be taken of specimens that cannot be transported off site.